MO966COGNITIVE FUNCTIONING AMONG VARIOUS MODALITIES OF RENAL REPLACEMENT THERAPY- ROLE OF RENAL TRANSPLANT. (29th May 2021) - Kaul, Anupma; Behera, Manas
Abstract: Background and Aims: Evidences have shown diverse responses on thedescription of cognitive function in patients who have undergone renaltransplantation. The present study examined the changes in cognitive functionamong ESRD patients on maintenance haemodialysis or on CAPD and followingthey post renal transplant. We also looked into the ccognitive status among frailand non frail ESRD patients and their performance in the post transplant period Method: 67 patients who were stable ESRD on thrice a week haemodialysis or onCAPD were investigated 6 months pre and post transplant using a battery ofneurophysiologic testing. Transplant function was assessed on regular interval andfollowing a stable graft function and on stable doses of immunosuppressive medication 6 months post transplant. Results: CAPD compared to HD had better preservation of cognitive functionsassessed 6 months after initiation of dialysis. There was statistically significantimprovement in general cognitive status performance (P < 0.001), motor speed, spatial reasoning, verbal memory and visual memory post transplant compared tothe pre transplant state. However, non-significant improvements were observed indomains of attention, executive functioning, language and verbal fluency. Theanxiety and depression scores did not show significant improvement despitetransplant. On the basis of fraility, frail individuals experienced less improvement in cognitive function as compared to non frail recipients in our study. Conclusion: The data demonstrate improvements in cognition following kidneytransplant and emphasize the reversibility of the memory problems evidencedamong patients on dialysis.Focus should be made for interventions in terms ofprevention of cognitive decline among frail patients very early in pre-end stage thus helping in overall outcomes post transplant.